Back disorders and nonneutral trunk postures of automobile assembly workers. - Punnett, Laura; Fine, Lawrence J.; Keyserling, W. M.; Herrin, G. D.; Chaffin, D. B. (Scandinavian Journal of Work, Environment & Health, 1991)
A case-referent study was conducted in an automobile assembly plant to evaluate the health effect of trunk postures, such as bending and twisting, that deviate from anatomically neutral. Cases of back disorders were all those of workers who reported back pain to the medical department in a ten-month period and met the severity criteria of an interview. The referents were randomly selected workers free of back pain according to medical department records, an interview, and an examination. For each of the final 95 cases and 124 referents, the job was analyzed for postural and lifting requirements with a video recording and software analysis system by analysts blinded to the case/referent status. Back disorders were associated with mild trunk flexion [odds ratio (OR) 4.9, 95% confidence interval (95% CI) 1.4-17.4], severe trunk flexion (OR 5.7, 95% CI 1.6-20.4), and trunk twist or lateral bend (OR 5.9, 95% CI 1.6-21.4). The risk increased with exposure to multiple postures and increasing duration of exposure.